(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Diplomatic immunities and privileges are a basic part of international relations because diplomats will not be disturbed by the legal system of the host state in performing their duties. This paper examines the extent, importance and restrictions of diplomatic immunities and privileges as provided in international law, in particular, in the Vienna Convention on Diplomatic Relations (1961). It explores the right and protection given to diplomats such as immunity against prosecution, inviolability of diplomatic premises, and freedom of communication. The paper describes the conflict between diplomatic immunity and accountability also, especially when diplomats abuse or engage in criminal acts. With an excellent overview of legal frameworks, case-studies and scholarly viewpoints, my paper seeks to offer a detailed insight into the extent to which the role of the diplomats is preserved and at what cost to the sovereignty of the host countries.